Aplikasi Prinsip Mazmur 2:11-12 dalam Peribadahan Kristen - Wisnu Prabowo (Sekolah Tinggi Teologi Berita Hidup, 2020)
Abstract: Worship and service are things that are very well known to Christians. In conducting worship and service there are several things that should be used as a basis for guidance. In Psalm 2: 11-12, written instructions for Christians in worship. This article examines the meaning of the sentence in Psalm 2: 11-12, which is,